If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -2) + 10 = 6(x + 4) + -8 Reorder the terms: 7(-2 + x) + 10 = 6(x + 4) + -8 (-2 * 7 + x * 7) + 10 = 6(x + 4) + -8 (-14 + 7x) + 10 = 6(x + 4) + -8 Reorder the terms: -14 + 10 + 7x = 6(x + 4) + -8 Combine like terms: -14 + 10 = -4 -4 + 7x = 6(x + 4) + -8 Reorder the terms: -4 + 7x = 6(4 + x) + -8 -4 + 7x = (4 * 6 + x * 6) + -8 -4 + 7x = (24 + 6x) + -8 Reorder the terms: -4 + 7x = 24 + -8 + 6x Combine like terms: 24 + -8 = 16 -4 + 7x = 16 + 6x Solving -4 + 7x = 16 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + 7x + -6x = 16 + 6x + -6x Combine like terms: 7x + -6x = 1x -4 + 1x = 16 + 6x + -6x Combine like terms: 6x + -6x = 0 -4 + 1x = 16 + 0 -4 + 1x = 16 Add '4' to each side of the equation. -4 + 4 + 1x = 16 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = 16 + 4 1x = 16 + 4 Combine like terms: 16 + 4 = 20 1x = 20 Divide each side by '1'. x = 20 Simplifying x = 20
| 4(20)-30+3(20)-10=100 | | 3n+4/2-8= | | 18=2n+7n | | 4x-30=3x-10 | | x(3+2)=x+5x | | 3(15-5)+10=2(15)+10 | | 18=9(8+x) | | x/2-10=-6 | | 10(k+9)=-10 | | 12-(3x-6)=8 | | ax+bw=-c | | 6.5x-32=2.5x+8 | | 4x+7y=51 | | -2=-3+x/11 | | -2=-4n-2 | | 5-8x=40-13x | | 3(x-5)+10=2x+10 | | 6(4x+5)=(x+8)+3 | | 4x-3+3x+8= | | p-6/2=-4 | | 7x+6-8x-6= | | 10+n/10=9 | | 19x-15=13+16x | | 7x+6+8x-6= | | 2x+3a=5a | | -19-p=-36 | | K-(-7)=-4 | | 6+0.60p=13.20 | | 6x-2=-4x+24 | | 40-4x=-7+7 | | 7-m=14 | | (1)/(3)=-(7)/(6)p+(5)/(6)p |